METHODOLOGY FOR ASSESSING TAX BENEFITS AT THE LOCAL LEVEL - L. Shevyrkov (Вестник университета, 2018)
The methods of assessment of efficiency of tax benefits operating at the local level are analyzed. Retrospective analysis allowed the author to identify the advantages and disadvantages of the proposed methods and to form the author’s vision on the feasibility of assessing tax benefits and preferences for local taxes and trade duties. The proposed method, the top quality will allow to estimate tax benefits to local authorities from the use of aggregate efficiency. The paper applies the formal-logical method, the system method, the method of mathematical modeling.